2023
DOI: 10.1200/jco.2023.41.6_suppl.671
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant immunotherapy in renal cell carcinoma: A systematic review and meta-analysis of randomized clinical trials.

Abstract: 671 Background: There has been interest in adjuvant immune checkpoint inhibition (ICI) following surgical resection in patients with high-risk renal cell carcinoma (RCC) given high recurrence rates and approvals of ICI in metastatic RCC. The primary objective of this analysis was to synthesize available data regarding the disease-free survival (DFS) benefit of adjuvant ICIs for patients with RCC. Methods: This systematic review was performed according to the PRISMA guidelines. The protocol was registered in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Two systematic reviews summarized the current landscape of immunotherapy trials. 14,15 Of the four phase-3 trials (CheckMate 914, IMmotion 010, KEYNOTE 564, and PROSPER), only KEYNOTE 564 showed an improvement in recurrence-free survival (RFS) in the immunotherapy arm (hazard ratio [HR] 0.63, 95% confidence interval [CI] 0.50-0.79). The pooled analysis revealed that most of the inconsistencies were due to variability between trials, and the pooled decrease in recurrence risk was 15% (pooled HR 0.85, 95% CI 0.69-1.04).…”
Section: Kidney Cancermentioning
confidence: 99%
“…Two systematic reviews summarized the current landscape of immunotherapy trials. 14,15 Of the four phase-3 trials (CheckMate 914, IMmotion 010, KEYNOTE 564, and PROSPER), only KEYNOTE 564 showed an improvement in recurrence-free survival (RFS) in the immunotherapy arm (hazard ratio [HR] 0.63, 95% confidence interval [CI] 0.50-0.79). The pooled analysis revealed that most of the inconsistencies were due to variability between trials, and the pooled decrease in recurrence risk was 15% (pooled HR 0.85, 95% CI 0.69-1.04).…”
Section: Kidney Cancermentioning
confidence: 99%